Pengukuran Perilaku Penggunaan Mobile Ticketing: Perspektif Unified Theory of Acceptance and Use of Technology - Fiska, Yushar; Wasilah (Jurnal Informatika, 2025)
The digital transformation of the public transportation sector has driven various service innovations, including the emergence of mobile ticketing applications that allow users to book tickets independently. Access by KAI is the official digital platform of PT Kereta Api Indonesia, offering services such as ticket booking, schedule checking, and access to e-boarding passes. Although the application has achieved a high number of downloads and users, some individuals have reported technical issues and suboptimal user experiences. This study investigates the influence of constructs within the UTAUT3 framework on behavioral intention and actual usage behavior of the Access by KAI application. UTAUT3, as applied in this study, includes the constructs from UTAUT2, with the addition of Personal Innovativeness in IT (PIIT) to reflect users’ inclination to adopt new technologies. A total of 211 respondents participated in this quantitative study, which was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that Facilitating Conditions and Personal Innovativeness in IT significantly affect Behavioral Intention, while Behavioral Intention and Habit significantly influence Use Behavior. Among all constructs, Habit was identified as the most dominant. The high R² value indicates strong explanatory power, while the Q² value confirms the model’s predictive relevance. This study reinforces the applicability of UTAUT3 in the context of mobile ticketing and provides practical insights for application developers to enhance user experience and engagement.